IMMU-13. Dual CTLA4/ PD-1 blockade improves survival for replication-repair deficient high-grade gliomas failing single agent PD-1 inhibition: An IRRDC study. (3rd June 2022) - Das, Anirban; Morgenstern, Daniel; Bianchi, Vanessa; Sudhaman, Sumedha; Edwards, Melissa; Stengs, Lucie; Larouche, Valerie; Samuel, David; Van Damme, An; Gass, David; Ziegler, David; Bielack, Stefan; et al.
Abstract: BACKGROUND : High-grade gliomas (HGG) with replication-repair deficiency (RRD) harbour high mutation burden (TMB) and are rapidly fatal following chemo-radiation approaches. Although hypermutation results in objective responses and prolonged survival in >30% of patients undergoing PD1-blockade, salvage following failure of PD1-inhibition remains a challenge. METHODS : We performed a real-world study of Ipilimumab (anti-CTLA4) in combination with Nivolumab/Pembrolizumab for patients failing single-agent PD1-inhibition. RESULTS : Among 68 consortium patients with relapsed HGG treated with single-agent PD1-inhibitors, progression was observed in 43 (63%). Ipilimumab was added to 20/43 (46.5%), 14 (32.5%) received best supportive care (BSC), and 9 (21%) received miscellaneous therapies. For patients receiving CTLA4/PD1-inhibition, median age at progression was 12.3-years (IQR: 9; 15.6). Time from anti-PD1 initiation to progression was 8-months (IQR: 3.8; 18.5). Germline predisposition was observed in all patients (CMMRD: 70%, Lynch: 25%, polymerase-proofreading deficiency: 5%). All HGG were hypermutant (median TMB: 182 mutations/Mb; IQR: 15.6; 369.4). Centralized radiology review revealed objective responses in 3/20 (15%, all ultra-hypermutant: 320, 496, 834 mutations/Mb), stable disease in 5 (25%), and 12 (60%) eventually progressed (iRANO). Following failure of PD1-blockade, estimated progression-free and overall survival at 18-months for patients receiving CTLA4/PD1-inhibition were 11% and 25%, respectively. Importantly, survival was superior to patients receiving BSC (median OS <1-month versus 12-months on CTLA4/PD1-inhibition; p<0.001). All patients receiving BSC died within 3.5-months, while 4/8 survivors were alive for >1-year on the anti-CTLA4/PD1combination (range:1-48 months). The combinational immunotherapy resulted in significant autoimmune toxicity in 11/20 (55%), warranting immunosuppressive therapy in all, and treatment abandonment in 6 patients. CONCLUSION : Combined CTLA4/PD1-blockade after failure of single-agent PD1-inhibition revealed objective responses and prolonged survival in an otherwise rapidly-fatal disease. This needs to be assessed in the context of significant autoimmunity, supporting the need for the current prospective trial (NCT04500548), and novel strategies to limit treatment-related toxicity.